Cardiovascular responses and the role of the neurohumoral cardiac regulation during digestion in the herbivorous lizard Iguana iguana - Guagnoni, Igor Noll [UNESP]; Armelin, Vinicius Araújo [UNESP]; Braga, Victor Hugo da Silva [UNESP]; Monteiro, Diana Amaral; Florindo, Luiz Henrique [UNESP] (The Company of Biologists, 2024)
Carnivorous reptiles exhibit an intense metabolic increment during digestion, which is accompanied by several cardiovascular adjustments responsible for meeting the physiological demands of the gastrointestinal system. Postprandial tachycardia, a well-documented phenomenon in these animals, is mediated by the withdrawal of vagal tone associated with the chronotropic effects of non-adrenergic and non-cholinergic (NANC) factors. However, herbivorous reptiles exhibit a modest metabolic increment during digestion and there is no information about postprandial cardiovascular adjustments. Considering the significant impact of feeding characteristics on physiological responses, we investigated cardiovascular and metabolic responses, as well as the neurohumoral mechanisms of cardiac control, in the herbivorous lizard Iguana iguana during digestion. We measured oxygen consumption rate (V_O2), heart rate (fH), mean arterial blood pressure (MAP), myocardial activity, cardiac autonomic tone, fH/MAP variability and baroreflex efficiency in both fasting and digesting animals before and after parasympathetic blockade with atropine followed by double autonomic blockade with atropine and propranolol. Our results revealed that the peak of V_O2 in iguanas was reached 24 h after feeding, accompanied by an increase in myocardial activity and a subtle tachycardia mediated exclusively by a reduction in cardiac parasympathetic activity. This represents the first reported case of postprandial tachycardia in digesting reptiles without the involvement of NANC factors. Furthermore, this withdrawal of vagal stimulation during digestion may reduce the regulatory range for short-term fH adjustments, subsequently intensifying the blood pressure variability as a consequence of limiting baroreflex efficiency.
Keywords: Autonomic control; Baroreflex; Cardiovascular adjustments; Green iguana; NANC factors; Postprandial tachycardia